The Indians' New World : Catawbas and Their Neighbors from European Contact through the Era of Removal - Merrell, James Hart, 1953- (Book collections on Project MUSE., 2009)
Merrell follows the Catawbas from their first contact with Europeans in the 16th century until they carved out a place in the American republic three centuries later. It is a story of Native agency, creativity, resilience, and endurance. Upon its original publication in 1989, this book helped signal a new direction in the study of Native Americans, serving as a model for their reintegration into American history.